Impact of a Three-Month Training Break on Swimming Performance in Athletes with Intellectual Disability - Glykeria Kyriakidou; George Tsalis; Christina Evaggelinou (Sports)
This study aimed to ascertain whether there were any differences in anthropometrics, heart rate, and swimming performance parameters in athletes with intellectual disabilities (ID) before and after a three-month training break. A total of 21 athletes participated in the study, comprising 16 males and 5 females, with a mean age of 28.3 ± 8.7 years. All participants had ID, and six of them had Down syndrome. The study participants were classified as S14 athletes from a local swimming club. All participants had a minimum of four years of swimming experience and attended two to three one-hour sessions per week for eight consecutive months. All athletes completed two trials of 25 m freestyle swimming, one at the end of a training session and the other at the beginning of a new session. The measurements included weight, body mass index (BMI), handgrip strength (HGS), heart rate (pre- and post-trial), performance (T25), stroke count (SC), stroke length (SL), stroke rate, and the SWOLF efficiency index. The results demonstrated statistically significant elevations in weight (80.2 ± 16.1 to 81.7 ± 15.9), BMI (26.8 ± 5.5 to 27.2 ± 5.5), T25 (33.1 ± 17.1 to 35.6 ± 18), SC (19.3 ± 6.1 to 20.7 ± 7.2), and SWOLF (52.4 ± 22.0 to 56.3 ± 25.2) and a reduction in SL (1.39 ± 0.48 to 1.27 ± 0.42). However, no significant differences were observed in the remaining parameters. Significant correlations were found for body weight, BMI, HGS, and SWOLF with T25 throughout the study. It was concluded that individuals with ID experienced a decline in 25 m swimming performance due to technical rather than physiological factors after three months of detraining.